Synchronous intermittent mandatory ventilation modes compared with patient triggered ventilation during weaning. Issue 3 (May 1995) - Dimitriou, G.; Greenough, A.; Griffin, F.; Chan, V.
Abstract : The efficacy of combining rate and pressure reduction during weaning by synchronous intermittent mandatory ventilation (SIMV) were compared with weaning by patient triggered ventilation (PTV) (pressure reduction alone) in two randomised trials. Regardless of ventilation mode, pressure was reduced to the same level according to the size of the infant. In the first trial, the SIMV rate was also reduced progressively to a minimum of 20 breaths/minute, and in the second to five breaths/minute. Forty premature infants aged 15 days of age or less were randomly allocated into each trial. No significant differences were found in the first trial between ventilation modes in either the duration of weaning or the number of infants in whom weaning failed. In the second trial, the duration of weaning was shorter by PTV than by SIMV (median 24 hours, range 7-432 v 50 hours, range 12-500; p < 0.05); weaning failed in two infants in the PTV group and in five in the SIMV group. It is concluded that weaning by a combination of pressure and rate reduction, such as can be achieved during SIMV, offers no significant advantage over pressure reduction alone.